Belonging: The Social Dynamics of Fitting In as Experienced by Hmong Refugees in Germany and Texas, by Faith G. Nibbs - Culhane-Pera, Kathleen A. (Refuge: Canada's Journal on Refugees, 2015)
Belonging: The Social Dynamics of Fitting In as Experienced by Hmong Refugees in Germany and Texas by Faith G. Nibbs Durham, NC: Carolina Academic Press, 2014